Beyond Budget Absorption: Analisis Rasio Keuangan dalam Mengungkap Optimalisasi Kinerja Keuangan dan Efektivitas Pengelolaan Anggaran pada Direktorat Jenderal Pajak - Misnawati; Perdana, Aditya; Amalia, Vera; Efrina, Liona (Magister Ilmu Akuntansi Universitas Jambi, 2026)
Financial performance assessments in the public sector have tended to focus on budget absorption rates as the main indicator of successful financial management. This approach does not fully reflect the quality of financial performance and the effectiveness of budget management in a comprehensive manner. This study aims to analyze the role of financial ratios in revealing the optimization of financial performance and the effectiveness of budget management at the Directorate General of Taxes (DGT). Using a quantitative approach, this study examines various public sector financial ratios, including ratios of effectiveness, efficiency, growth, and financial independence, as performance evaluation instruments that go beyond mere budget absorption measures. The research data was sourced from the DJP's audited financial reports during the observation period. The analysis was conducted using inferential statistical methods to identify the relationship and contribution of financial ratios to the effectiveness of budget management. The results show that the optimization of financial performance as reflected in financial ratios has a significant effect on the effectiveness of budget management, while the level of budget absorption does not always substantially reflect the quality of financial performance. These findings emphasize the importance of shifting the paradigm of public sector financial performance evaluation from a compliance orientation to a performance and value-based approach. This study contributes to the enrichment of public sector accounting literature by offering a more comprehensive financial performance evaluation framework and providing policy implications for strengthening financial governance and fiscal accountability within the Directorate General of Taxes.